Graphical Approach to Compare Concentration Constants of Hill and Michaelis-Menten Equations - Elena V. Emelyanova (Journal of Biotechnology and Biomedical Science, 2018)
The aim of present study was to describe the graphical technique how to go from Hill concentration constant to Michaelis constant. To compare enzymatic processes, the kinetics of which is subjected to different regularities, it is possible to use constants that characterize catalytic activity (Vmax) and concentration constants that are the substrate concentration at which the rate of the enzymatic process is equal to a half of maximum permissible rate. Concentration constants are S0.5 for Hill equation and Km for Michaelis-Menton equation. The graphical approach was proposed in order to go from concentration constant of Hill equation to Michaelis concentration of the process that could be characterized by the same catalytic activity (the same values of minimum and maximum rates) similar to that observed in the process described by Hill equation.
Keywords: graphical approach